2020
DOI: 10.1186/s12974-020-01825-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid findings in patients with myelin oligodendrocyte glycoprotein (MOG) antibodies. Part 2: Results from 108 lumbar punctures in 80 pediatric patients

Abstract: Background: New-generation, cell-based assays have demonstrated a robust association of serum autoantibodies to full-length human myelin oligodendrocyte glycoprotein (MOG-IgG) with (mostly recurrent) optic neuritis, myelitis, and brainstem encephalitis, as well as with neuromyelitis optica (NMO)-like or acute-disseminated encephalomyelitis (ADEM)-like presentations. However, only limited data are yet available on cerebrospinal fluid (CSF) findings in MOG-IgG-associated encephalomyelitis (MOG-EM; also termed MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 88 publications
4
45
0
1
Order By: Relevance
“…Although the differential cell count is dominated by lymphocytes in MS, we showed that in some cases neutrophils may occur. Knowledge on leukocyte subtypes is of importance for differential diagnosis of MS, as NMOSD or MOGAD are occasionally associated with a predominant presence of neutrophils (27,40). Interestingly, we observed that the presence of monocytes/macrophages was associated with conversion to CDMS.…”
Section: Discussionmentioning
confidence: 67%
“…Although the differential cell count is dominated by lymphocytes in MS, we showed that in some cases neutrophils may occur. Knowledge on leukocyte subtypes is of importance for differential diagnosis of MS, as NMOSD or MOGAD are occasionally associated with a predominant presence of neutrophils (27,40). Interestingly, we observed that the presence of monocytes/macrophages was associated with conversion to CDMS.…”
Section: Discussionmentioning
confidence: 67%
“…In many respects, CSF findings in MOG-EM share much more similarities with NMOSD than with MS. Our data may help to improve the differential diagnosis of MOG-EM and MS and to extend our understanding of the immunopathology of this newly described entity. A detailed analysis of the CSF findings in pediatric patients with MOG-EM can be found in part 2 of this article series [83].…”
Section: Resultsmentioning
confidence: 99%
“…A small subset of MS patients are seropositive for MOG Ab 47–49 . In contrast to MS, CSF findings in adult and paediatric MOGAD cohorts show that OCBs are less commonly observed in MOGAD compared to MS, and are seen in 10–30% of patients 50,51 . Radiological differences highlight that MOGAD and NMOSD patients with ON are more likely to have bilateral and longitudinally extensive optic nerve lesions compared to MS patients with ON 52 .…”
Section: Clinical and Pathological Features Of Autoimmune Demyelinating Disordersmentioning
confidence: 98%
“…[47][48][49] In contrast to MS, CSF findings in adult and paediatric MOGAD cohorts show that OCBs are less commonly observed in MOGAD compared to MS, and are seen in 10-30% of patients. 50,51 Radiological differences highlight that MOGAD and NMOSD patients with ON are more likely to have bilateral and longitudinally extensive optic nerve lesions compared to MS patients with ON. 52 Comparatively, MOGAD patients with ON more frequently experienced lesions in the anterior visual pathway relative to NMOSD patients with ON in which lesions were observed posteriorly including the optic chiasm and optic tract.…”
Section: Clinical and Pathological Features Of Autoimmune Demyelinating Disorders Multiple Sclerosismentioning
confidence: 99%